A protocol and analysis of year-long simulations of global storm-resolving models and beyond - Daisuke Takasuka; Masaki Satoh; Tomoki Miyakawa; Chihiro Kodama; Daniel Klocke; Bjorn Stevens; Pier Luigi Vidale; Christopher R. Terai (Progress in Earth and Planetary Science)
Abstract We propose a protocol to evaluate and analyze year-long simulations of global storm-resolving models (GSRMs). The proposed protocol complements an earlier 40-day simulation protocol under the DYAMOND (DYnamics of the Atmospheric general circulation Modeled On Non-hydrostatic Domains) project to allow the analysis of the seasonal cycle and associated climatic relevant phenomena. This intercomparison aims to reveal how GSRMs, which can simulate mesoscale convective systems (MCSs) in the global domain, reproduce atmospheric large-scale structures related to convection beyond month-long simulations. The intercomparison for one-year simulations is conducted by either atmosphere-only models or atmosphere–ocean coupled models with atmospheric horizontal mesh sizes less than 5 km. We recommend the continuous four seasons from March 2020 to February 2021 as a target period for the intercomparison but with options for many groups to join more flexibly. The output variables are collected at 0.25° resolution, and archives of a small set of native grid variables are encouraged to analyze tropical cyclones and MCSs. Through the proposed global storm-resolving simulation, we will evaluate the climatological distributions of the atmospheric large-scale circulations, such as the Intertropical Convergence Zone (ITCZ), monsoon, midlatitude jets, their time evolution, and the upscale impacts on them. We present sample analyses from a one-year simulation using the 3.5 km mesh Nonhydrostatic Icosahedral Atmospheric Model (NICAM), revealing the realistic zonal contrast of tropical precipitation, no double ITCZ structure, the reasonable midlatitude jet position and intensity but a weak bias of storm track activities, and a warm bias over the Eurasia during boreal winter. We also clarify the cross-scale interaction, such as the effects of cold pools on mean precipitation over the Maritime Continent through the precipitation diurnal cycle and the effects of resolved gravity waves on midlatitude mean flows. The proposed one-year simulation protocol is referred to as the “Sendai Protocol.” This protocol is not unique or definite for evaluating GSRMs; we prospect a hierarchical set of experiments from short-term to multi-year simulations as GSRM intercomparisons. A protocol and analysis of year-long simulations of global storm-resolving models. Daisuke Takasuka, Masaki Satoh, Tomoki Miyakawa, Chihiro Kodama, Daniel Klocke, Bjorn Stevens, Pier Luigi Vidale, Christopher R. Terai. Progress in Earth and Planetary Science. Sample analysis of a one-year experiment with the global storm-resolving model, Nonhydrostatic Icosahedral Atmospheric Model (NICAM). Top: seasonal mean precipitation obtained from the (left) the Global Precipitation Climatology Project (GPCP) product and (right) 3.5-km NICAM simulation for (a, b) March-April-May, (c, d) June-July-August, (e, f) September-October-November, and (g, h) December-January-February in 2011-2012. Bottom: time-latitude diagrams of the monthly mean precipitation averaged from 160°E to 140°W over the Pacific for the (left) GPCP product and (right) 3.5-km NICAM simulation